Fin whale (Balaenoptera physalus) migration in Australian waters using passive acoustic monitoring - Aulich, Meghan; McCauley, Robert; Saunders, Ben; Parsons, Miles (NATURE PUBLISHING GROUP, 2019)
© 2019, The Author(s). The fin whale is a globally endangered species and is listed as threatened in Australia, however no peer-reviewed studies are available to indicate the migratory movements of the species in Australian waters. This study uses passive acoustic monitoring as a tool to identify the migratory movements of fin whales in Australian waters. Sampling was conducted from eight locations around Australia between 2009 and 2017, providing a total of 37 annual migratory records. Taken together, our observations provide evidence of fin whale migration through Australian waters, with earliest arrival of the animals recorded on the Western Australian coast, at Cape Leeuwin in April. The whales travel through Cape Leeuwin, migrating northward along the Western Australian coast to the Perth Canyon (May to October), which likely acts as a way-station for feeding. Some whales continue migrating as far north as Dampier (19°S). On Australia’s east coast, at Tuncurry, fin whale seasonal presence each year occurred later, from June to late September/October. A total of only 8,024 fin whale pulses were recorded on the east coast, compared to 177,328 pulses recorded at the Perth Canyon. We suggest these differences, as well as the spatial separation between coasts, provide preliminary evidence that the fin whales present on the east and west coasts constitute separate sub-populations.